Reelin Proteolysis Affects Signaling Related to Normal Synapse Function and Neurodegeneration - Lussier, April L.; Weeber, Edwin J.; Rebeck, G. William (Frontiers in Cellular Neuroscience, 2016)
Reelin is a neurodevelopmental protein important in adult synaptic plasticity and learning and memory. Recent evidence points to the importance for Reelin proteolysis in normal signaling and in cognitive function. Support for the dysfunction of Reelin proteolysis in neurodegeneration and cognitive dysfunction comes from postmortem analysis of Alzheimer’s diseases (AD) tissues including cerebral spinal fluid (CSF), showing that levels of Reelin fragments are altered in AD compared to control. Potential key proteases involved in Reelin proteolysis have recently been defined, identifying processes that could be altered in neurodegeneration. Introduction of full-length Reelin and its proteolytic fragments into several mouse models of neurodegeneration and neuropsychiatric disorders quickly promote learning and memory. These findings support a role for Reelin in learning and memory and suggest further understanding of these processes are important to harness the potential of this pathway in treating cognitive symptoms in neuropsychiatric and neurodegenerative diseases.